Impact of poultry manure on fruit quality attributes and nutrient status of guava (Psidium guajava.) cv. L 49 plant - SHARMA, AKASH; WALI, V K; BAKSHI, PARSHANT; SHARMA, VIKAS; SHARMA, VIKAS; BAKSHI, MANISH; RANI, SOHNIKA (The Indian Journal of Agricultural Sciences, 2016)
Management of nutrients in guava refers (Psisdium guajava L.) to maintenance of the soil fertility and plant nutrient supply to an optimum level for sustaining the desired crop productivity and fruit quality through optimization of benefits from all the possible sources in an integrated manner. Qualitative and quantitative attributes of guava fruit cv. Lucknow 49 were analyzed with the aim of corresponding the nutrients to the quality of the fruit where fertilizer dose of N were manipulated in different treatments. Soil and leaf study were conducted to analyze the status of nutrients in guava. The pooled analysis of two year data indicated that after fruit harvest the highest soil organic carbon (0.72%) was obtained with the treatment comprising (Azotobacter + 100% N poultry manure. Soil N and P (271.36 and 19.86 kg/ha), Ca and Mg (7.12 and 2.82 meq 100/g soil), respectively, were recorded maximum with the treatment comprising Azotobacter + 50% N poultry manure + 50% N urea. The same treatment also showed highest leaf N and P (1.78 and 0.16%), Ca and Mg (2.09 and 0.91%) contents, respectively, on dry weight basis. The highest soil K (148.53 kg/ha) and leaf K (1.27% on dry weight basis) contents were obtained with the application of Azotobacter + 75% N poultry manure + 25% N urea. The pooled analysis of two year data also indicated that 50% N poultry manure + 50% N urea showed highest fruit yield (42.89 kg/plant), maximum fruit length (8.47 cm), breadth (8.02 cm), weight (248.80 g) and pulp weight (218.68 g) while, Azotobacter + 50% N/tree through FYM + 50% N/tree through inorganic fertilizer showed highest TSS (13.01Â°B), total sugars (8.68%) and minimum physiological loss in weight (13.20%) after 10 days during storage under ambient conditions. The results suggested that fertilization of guava with chemical fertilizers can be minimized when nitrogen is applied half with poultry manure and half with urea augmented with Azotobacter.